Peran Gereja dalam Membangun Solidaritas Sosial Jemaat: Kajian Sosiologi Agama Émile Durkheim dan Teologi Komunitas Dietrich Bonhoeffer - Hiruniko Ruben (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This study examines the role of the church in building congregational social solidarity through a dialogue between Émile Durkheim’s sociology of religion and Dietrich Bonhoeffer’s theology of community. It responds to the tendency to reduce congregational solidarity to worship attendance, programmatic activity, or occasional charity, whereas genuine solidarity requires relational formation, trust, shared responsibility, and public witness. Using library research and conceptual-theological analysis, the study engages classical works and recent scholarship on religion, social capital, congregational cohesion, and ecclesial community. The findings show that the church functions as a relational infrastructure that forms belonging and participation, yet such solidarity remains ambivalent when it is not theologically corrected. Durkheim clarifies the social power of ritual and collective consciousness, while Bonhoeffer insists that ecclesial solidarity must be grounded in Christ, forgiveness, service, and life for others. The study concludes that a healthy church is not merely cohesive, but transforms internal cohesion into restorative public witness within fragmented plural societies, where Christian community must become critical, open, transformative, and contextually accountable to vulnerable persons and the wider public as gospel praxis.